International Import and Export Trade Forecasting Algorithm Based on Heterogeneous Dynamic Edge Computing System. (20th March 2021) - Yang, Yingfei
Abstract : As a new computing model, how to use edge computing to forecast import and export trade has become an issue of concern. This research mainly discusses the prediction algorithm of international import and export trade based on heterogeneous dynamic edge computing system. The dynamic task migration system studied in this paper mainly includes four parts: edge computing environment simulator, task generator, resource predictor, and migration decision maker. These four parts are not independent modules in the working process; they will interact with each other in the edge computing environment. In the data processing offloading strategy, the customs business personnel transfer the trade data that need to be predicted to the edge device cluster through the mobile terminal. After receiving the data transmitted by the business personnel, the edge device cluster uses data processing technology to process the data. After the data processing operation is completed, the processed data is directly used for prediction work. After the prediction work is completed, the data and results are uploaded to the central server. Finally, after the prediction work is completed, the edge device will feed back the prediction result to the mobile terminal and display the result on the user interface through the mobile terminal so that business personnel can understand the trade risk status. From August 2018 data application period, the monthly data of the import and export trade volume for the subsequent time span of ten years were regularly forecasted, and the correlation coefficient was still over 83%, and the RMSE also dropped significantly. The system designed in this study can effectively predict the annual estimated value of various economic indicators of international import and export trade.